Examining the association between perceived stigma, its correlates, and restrictions in participation among persons with disabilities in Nepal: a cross-sectional study - Hridaya Raj Devkota; Sasmita Poudel; Mohan Krishna Shrestha; Radhika Upreti Oli; Nabin Kumar Rai; Manish Poudel; Pradeep Banjara; Catherine Malla; Yadira Perez Hazel; Anjila Dahal; Reeta Gurung (BMC, 2024)
Abstract Background Disability stigma in low- and middle-income countries is one of the most persistent and complex barriers limiting persons with disabilities (PwDs) from enjoying their rights and opportunities. Perceived stigma among PwDs and its impact on participation restriction is rarely assessed in Nepal. Objective This study aimed to measure the extent of perceived stigma by PwDs, identify its relationships with specific demographic factors, and assess the impact on social participation. Methods A cross-sectional survey was conducted between May and July 2022 among PwDs in Nepal, with a sample of 371. The Explanatory Model Interview Catalog (EMIC) stigma scale and P-scale suitable for people affected by stigmatized conditions were used, and the generated scores were analyzed. One-way ANOVA was performed to determine group differences for sociodemographic variables, and linear regression and correlational analysis were used to identify their association and measure the strength and direction of the relationship. Results The mean stigma score was 16.9 (SD 13.8). 42% of respondents scored higher than the mean. The scores differed significantly by disability type, caste and ethnicity, education, occupation, and household wealth. Over 56% reported participation restriction, and 38% had severe/extreme restriction. Approximately 65% of participants with intellectual disabilities, 53% with multiple disabilities, and 48.5% of persons with severe or profound disabilities experienced severe or extreme restrictions. Perceived stigma had a positive correlation with Disability type (r = 0.17, P < 0.01) and negative correlations with Severity of disability (r= -0.15, P < 0.05), and Household wealth (r= -0.15, P < 0.01). Education was inversely associated with both stigma (r= -0.24, P < 0.01), and participation restriction (β= -9.34, P < 0.01). However, there was no association between stigma and participation restriction (β= -0.10, P > 0.05). Conclusion All participants exhibited stigma in general; however, the severity varied based on disability type, level of education, and sociocultural circumstances. A large proportion of participants reported facing a high degree of restrictions in participation; however, no association was detected between perceived stigma and participation restriction. A significant negative linear correlation was observed between education and participation restriction. Stigma reduction programs focusing on education and empowerment would be especially important for overcoming internalized stigma and increasing the participation of PwDs.